Sustainability certifications and financial profitability : an analysis on palm oil companies in Malaysia - Hafizuddin-Syah B.A.M,; S. Shahida,; Siti Hanisah Fuad, (Penerbit Universiti Kebangsaan Malaysia, 2018)
As the second largest palm oil producer in the world, Malaysian palm oil industry has contributed significantly to the national GDP. However, this industry has been under criticism for serious deforestation and open burning activities, which obviously opposing to the objective of the oil palm Good Agricultural Practice on zero burning. As a result, sustainability certification of Roundtable Sustainable Palm Oil and Malaysia Sustainable Palm Oil had been introduced towards achieving sustainable development governance in this industry and fulfilling the needs of importing countries on certified palm oil. However, the number of companies with sustainability certification is relatively low due to the concern on potential additional cost, which then could affect firm profitability. Therefore, this study aims to examine the impact of sustainability certification on financial profitability among 39 palm oil companies in Bursa Malaysia, from 2009 to 2016. Based on the GLS estimation model, the finding shows that the profitability of firms with sustainability certification is almost 2% higher than firms without certification. The finding of this study provide useful input for industry players and could encourage palm oil companies to subscribe sustainability certifications to improve their sustainability practices and good governance as well as increase their profits.